การบริหารความได้เปรียบทางการแข่งขันเพื่อความสำเร็จ ในการดำเนินงานของธุรกิจขนาดย่อมในเขตภาคเหนือของประเทศไทย: THE MANAGEMENT OF SMALL ENTERPRIESES TO ACHIEVE COMPETITIVE ADVANTAGES NORTHERN OF THAILAND - Pongwiritthon, Ratthanan; Utama-ang, Surachai (Asian Health, Science and Technology Reports, 2011)
This research aims at studying the management to achieve competitive advantages, the success of business management, the impact and relationship between the management to achieve competitive advantages and the impact of management to achieve competitive advantages. From the questionnaire collected data from 400 small enterprises’ entrepreneurs who run business in 9 provinces of northern of Thailand, the researcher found out that there are the management to achieve competitive advantages and the success in overall operations are in high level. Also the relationship in each type of small entrepreneurs business in each area has no different in overall of the management to achieve competitive advantages. In term of problem and obstacle arose from interviewing the thought leader, the researcher found out that to run small entrepreneurs business, there are not different in term of marketing and innovation in the manufacturing process. In term of financial matters, there are no account operating and cost management has no network of partners.